Inovasi Sapu Lidi Dalam Implementasi Literasi Digital di SMP Negeri 2 Selomerto Wonosobo - Yuni Tri Supanti Budiyanto (Universitas Sarjanawiyata Tamansiswa, 2023)
This study aims to obtain a description of the planning analysis, to analyze the organization, to analyze the supervision, to analyze the evaluation, and to find out the supporting and inhibiting factors for the implementation of the LIDI SAPU Innovation at SMP Negeri 2 Selomerto. This study uses qualitative research in order to obtain in-depth information regarding the LIDI BROOM Innovation at SMP Negeri 2 Selomerto Wonosobo. In this study, the data sources were school principals, innovator teachers, teachers, students and librarians. Activities in data analysis consist of data collection, data reduction, data presentation, and conclusions/verification. There are 4 pillars of digital literacy for students and teachers which will be improved towards this innovation, namely: 1) Increasing digital culture 2) Increasing digital savety 3) Increasing digital ethics 4) Increasing digital skills. The results of the research regarding the Implementation of the LIDI SAPU Innovation in the implementation of digital literacy for teachers and students at SMP Negeri 2 Selomerto Wonosobo, it was concluded that the management process had been well implemented from the elements of planning (planning), organizing (organizing), implementing (actuating), Supervision ( controlling), and Evaluation (evaluating). SAPU LIDI's innovation makes a positive contribution to the world of education in accordance with the Sustainable Development Goals (SDGs) related to guaranteeing literacy and numeracy capabilities by applying service methods by applying the 4 pillars of digital literacy, namely: Digital Culture, Digital Safety, Digital Ethics, and Digital Skills.